2021
DOI: 10.1371/journal.pone.0252607
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate proteoglycans in beta cells provide a critical link between endoplasmic reticulum stress, oxidative stress and type 2 diabetes

Abstract: Heparan sulfate proteoglycans (HSPGs) consist of a core protein with side chains of the glycosaminoglycan heparan sulfate (HS). We have previously identified (i) the HSPGs syndecan-1 (SDC1), and collagen type XVIII (COL18) inside mouse and human islet beta cells, and (ii) a critical role for HS in beta cell survival and protection from reactive oxygen species (ROS). The objective of this study was to investigate whether endoplasmic reticulum (ER) stress contributes to oxidative stress and type 2 diabetes (T2D)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 72 publications
1
22
0
Order By: Relevance
“…Additionally, in 1995, Cechowska-Pasko et al [ 62 ], in an in vivo study on diabetic rats, showed that the level of GAGs significantly decreased (by 50% to 70%) in the skin of the rats. In 2021, Dhounchak et al [ 63 ] showed that β-cell failure in T2DM results from HS/HSPGs deficiency; this paper complements previous articles that discussed the importance of preserving HS during inflammatory processes and viral infections [ 5 , 6 ].…”
Section: Covid-19 Severity D-xylose and Type 2 Diabetes: Mechanism By...supporting
confidence: 68%
“…Additionally, in 1995, Cechowska-Pasko et al [ 62 ], in an in vivo study on diabetic rats, showed that the level of GAGs significantly decreased (by 50% to 70%) in the skin of the rats. In 2021, Dhounchak et al [ 63 ] showed that β-cell failure in T2DM results from HS/HSPGs deficiency; this paper complements previous articles that discussed the importance of preserving HS during inflammatory processes and viral infections [ 5 , 6 ].…”
Section: Covid-19 Severity D-xylose and Type 2 Diabetes: Mechanism By...supporting
confidence: 68%
“…22,32,93,166 Conversely, it seems that HS and dysfunction of the GL play a role in the etiology of DM in the first place. Recent reviews described that human beta cells have a remarkably high intracellular level of highly sulfated HS, 66,86,162 protecting cells in the pancreatic islet from ROS and cell death. 167 This protective anti-apoptotic effect is neutralized when nearby autoreactive T cells secrete HPSE that subsequently degrade HS, leading to an onset of Type 1 DM (T1D).…”
Section: Pathophysiology Of Covid -19mentioning
confidence: 99%
“…DM is a clinically well‐defined metabolic disease connected with insulin absence or resistance in which obesity, hyperglycemia, dyslipidemia, and chronic low‐grade pancreatic islets inflammation contribute directly or indirectly to beta‐cell failure 162 . Patients with DM display a tendency to develop vascular complications, such as microalbuminuria, retino‐, and nephropathy, elevated the risk of atherothrombotic cardiovascular and cerebrovascular events 14,56 .…”
Section: Pathophysiology Of Covid‐19mentioning
confidence: 99%
See 2 more Smart Citations